10.1016/s0029-7437(07)70193-3 (CrossRef Listing of Deleted DOIs, 2000)
Objective This review investigates the potential of photobiomodulation (PBM) as a therapeutic option for asthma management and further examines the immune and molecular mechanisms that may support its therapeutic effects. Methods A comprehensive literature review was conducted in PubMed, Scopus, Google Scholar, EMBASE, Web of Science, CINAHL, and MEDLINE. A set of keywords covering the topic was used to extract relevant articles from 1990 to April 2026. The selected articles were used to synthesize a scientific narrative based on the critical analysis of extracted data, summarized in tables and illustrated in detail. Results Emerging data from preclinical and clinical evaluations demonstrate that PBM acts as a highly viable, non-invasive therapeutic modality that counteracts the core immune-mediated mechanisms driving chronic airway inflammation in asthma. In most experimental asthma models, radiant energies of 3J and 5J significantly mitigate the Th2-dominated hypersensitivity response by suppressing critical Type 2 inflammatory cytokines, specifically interleukin (IL)-4, IL-5, and IL-13, and by reducing eosinophil recruitment and goblet cell hyperplasia. Beyond standard immune modulation, PBM supports non-immune structural tissue preservation by enhancing the expression of anti-inflammatory, anti-apoptotic, and antioxidant genes in epithelial, endothelial, and fibroblast cells, thereby reducing collagen deposition and alleviating subepithelial fibrosis. In clinical settings, supplementary near-infrared light applications and laser acupuncture have demonstrated marked efficacy, significantly reducing asthma severity grades, daily/nocturnal symptoms, and exacerbations, while establishing substantial improvements in asthma control and lung function. The review further discusses potential limitations, safety considerations, and directions for future research. Conclusions PBM is a potentially affordable and relatively safe adjunct therapy for asthma, supported by preclinical evidence warranting further research. Important aspects such as dosimetry, irradiation geometry, tissue optics, and the realistic delivery of photons to intrathoracic airways are still underdeveloped and require carefully designed clinical trials. Future health economic studies to assess the comparative cost-benefit of PBM are also warranted.